IMPROVEMENT OF MATHEMATICS LEARNING PROCESS AND OUTCOMES USING THE MAKE A MATCH MODEL ASSISTED BY CONGKLAK MEDIA IN GRADE III SDN 174/II APUNG ILIR: PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL MAKE A MATCH BERBANTU MEDIA CONGKLAK DI KELAS III SDN 174/II APUNG ILIR - Siti Nurhaliza; Nurlev Avana; Aldino Aldino (SOSIOEDUKASI, 2025)
This research aims to improve the quality of the mathematics learning process and outcomes of grade III students of SDN 174/II Apung Ilir through the application of the Make a Match learning model assisted by congklak media. The method used is Class Action Research (PTK) which is carried out in two cycles, with each cycle including the stages of planning, implementation, observation, and reflection. Data collection is carried out through learning outcome tests, student activity observation sheets, and documentation. The results showed a significant increase in both indicators measured. The average score of student learning outcomes increased from 75.00 in the first cycle to 83.18 in the second cycle, with a learning completeness rate of 90.91%. Student activities also showed development, from the category of "quite active" in cycle I to "very active" in cycle II. These findings are in line with the results of previous research showing that the application of an interactive learning model with the support of contextual media is able to increase motivation, engagement, and understanding of mathematical concepts. Therefore, the Make a Match model assisted by congklak media is recommended as an alternative to mathematics learning strategies in elementary schools to encourage active participation and improve students' academic achievement.